2016
DOI: 10.1186/s13638-016-0653-x
|View full text |Cite
|
Sign up to set email alerts
|

Service-oriented mobile multimedia cooperative storing and delivery scheme based on opportunistic cloud coding and content-centric cloud compression

Abstract: In order to improve the quality of multimedia communication and mobile users, the work efficiency of the cloud platform, the service-oriented mobile multimedia cooperative storing, and the delivery scheme were proposed based on opportunistic cloud coding and content-centric cloud compression. Firstly, according to the video frame and the multimedia content centric, the multimedia data compression algorithm was established based on time domain and frequency domain, which combined the image pixel scale and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the future, minimization of packet delay and loss will increase the user satisfaction for cloud services and also cloud service provider will give compensation to the user if the QoS of the services are low as per the SLA. The compression of video and image cloud also decreases the QoE of users so the development of new storage algorithms which compresses the size of the file for storage without affecting the quality of the file is better for user satisfaction and also for cloud management (Lin 2016, Castiglione et al 2015. Integration of social media clouds for video hosting is required for long time duration of HD video hosting.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…In the future, minimization of packet delay and loss will increase the user satisfaction for cloud services and also cloud service provider will give compensation to the user if the QoS of the services are low as per the SLA. The compression of video and image cloud also decreases the QoE of users so the development of new storage algorithms which compresses the size of the file for storage without affecting the quality of the file is better for user satisfaction and also for cloud management (Lin 2016, Castiglione et al 2015. Integration of social media clouds for video hosting is required for long time duration of HD video hosting.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…It can be concluded that the receiver can correctly decode the mobile multimedia stream, such as the formula (7). Data packet number of one frame [10,100] Size of data packet 1 kb…”
Section: Opportunistic Wavelet Multimedia Mobility Modelmentioning
confidence: 99%
“…The video processing algorithm was mapped onto a learning method to improve machine to the parallel reconfigurable computing architecture [9]. The author of article [10] proposed the service-oriented mobile multimedia cooperative storing, and the delivery scheme to improve the quality of multimedia communication and mobile users, the work efficiency of the cloud platform. The security and privacy issues of multimedia services were investigated in article [11] by studying a newly emerging multimedia-oriented mobile social network, which helps users receive multimedia services not only from their online social communities.…”
Section: Introductionmentioning
confidence: 99%